Il commercio infame: Antischiavismo e diritti dell'uomo nel Settecento italiano The Infamous Commerce: Antislavery and Rights of Men in the 18th Century Italy - Alessandro Tuccillo (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2013)
The legitimacy of slavery, deeply rooted in classical and Christian culture, was called into question starting from the 18th century. It was a slow process, that had to relate to the peculiar forms the slavery institution got with the European colonisation of America in the Modern Age, that is the workforce imported from sub-Saharan Africa. This process was influenced by economic and political aspects and got a turning point on the intellectual history point of view when the problem of the universal acknowledgment of natural rights of men arose. This history did not concern the colonial powers solely, and this volume explores an unknown field about it, that is the Italian Enlightenment culture's contribution to the transnational antislavery thought. In their writings, the Illuministi - and Southern reformers most of all - bumped into the colonial slavery matter, focusing on economic science, history, ancient and contemporary political treaties and on the definition of reforms inspired by the principles of natural rights. The black slave got the anti-model of the human emancipation project of political Enlightenment and, at the end of the century, of the revolutionary «regeneration». Human trafficking and the violation of natural rights were, for Italian antislaverists, the «infamous commerce».